A biodegradable rectal balloon implant to protect the rectum during prostate cancer radiotherapy for a patient with active Crohn's disease. (June 2018) - Vanneste, Ben G.L.; Van Limbergen, Evert J.; van de Beek, Kees; van Lin, Emile; Lutgens, Ludy; Lambin, Philippe
Highlights: Active inflammatory bowel disease is an exclusion criterion for high-dose radiotherapy. A rectum spacer was inserted between the prostate and the rectal wall. The rectum spacer pushes the rectum outside of the high-dose area. No rectal toxicity of the radiotherapy or toxicity ﬂare of the IBD was observed. Abstract: Background: Radiotherapy in patients with active inflammatory bowel disease (IBD) is usually considered an absolute exclusion criterion for prostate cancer radiotherapy treatment. There are no reports available on the use of a biodegradable rectal balloon implantation (RBI) in patients with active IBD for prostate cancer radiotherapy. Case presentation: We report on a patient with high-risk prostate cancer with the comorbidity of an active IBD with pancolitis location. He was treated with neo-adjuvant hormonal therapy and high-dose external beam radiotherapy to the prostate and the seminal vesicles. Before radiotherapy treatment, a biodegradable RBI was implanted between the prostate and the anterior rectal wall to push the rectum outside of the high-dose area. This patient at high-risk for rectal toxicity was successfully irradiated to his prostate with only a grade I urinary toxicity, no acute rectal toxicity or toxicity flare of the IBD. Conclusions: This case describes the use of a RBI implantation in patients with active IBD for prostate cancer radiotherapy. The use of a biodegradable RBI proved to be a promised solution for such patients, and have to be further investigated.